ICARE_08_12_025 ... : [Paysages, voyages, bateaux, divers] ... - inconnu], [Photographe (NAKALA - https://nakala.fr (Huma-Num - CNRS), 2021)
Navire pris dans la banquise ... : Source: CNRS, UMR CReAAH, Archives, ICARE_PV0812025 ...